Experiences of front-line nurses caring for patients with COVID-19 in Bangladesh: A qualitative study - Rony, Moustaq Karim Khan; Bala, Shuvashish Das; Rahman, Md. Moshiur; Dola, Afrin Jahan; Kayesh, Ibne; Islam, Md. Tawhidul; Tama, Israth Jahan; Shafi, Emdadul Haque; Rahman, Shamima (Belitung Raya Foundation, Indonesia, 2021)
Background: As the incidence of COVID-19 is increasing, the Bangladesh government has announced a countrywide shutdown instead of a lockdown. Consequently, front-line healthcare workers, particularly nurses, are confronting more challenging situations at work. Objective: This study aimed to explore front-line nurses’ experiences caring for patients with COVID-19 in Dhaka, Bangladesh. Methods: A qualitative descriptive study was conducted among front-line nurses caring for patients with COVID-19. Twenty nurses were purposively chosen from January to March 2021 to participate in semi-structured online interviews. Interviews on audio and video were collected, analyzed, interpreted, transcribed verbatim, and verified by experts. Thematic analysis was used. Results: Nine themes emerged and were grouped into negative and positive experiences. The themes of negative experiences include lack of necessary medical equipment, use of non-standard personal protective equipment, work overload, long working hours, poor working environment, and lack of quality of nursing care. The positive experiences include feeling self in a patient position, nurses’ coping strategy in COVID-19 patient care, and establishing emotional control. Conclusion: The study results encourage national and international health care professionals to cope with adverse working environments. Also, the findings provide nurses with techniques for dealing with any critical situation, controlling patients’ emotions, and how empathy increases self-confidence and patient care. The research should also be used to enhance government policy, nursing council policy, ministry of health policy, and other healthcare agencies.